Crimean-Congo Hemorrhagic Fever Virus among Goats, Southern Bhutan - Sangay Rinchen; Yoshihiro Kaku; Eunsil Park; Puspa Maya Sharma; Dawa Tshering; Tenzinla Tenzin; Aya Matsuu; Akiko Okutani; Ken Maeda; Shigeru Morikawa (Emerging Infectious Diseases)
We conducted serosurveillance for Crimean-Congo hemorrhagic fever virus (CCHFV) among goats in southern Bhutan. Testing serum samples from 472 goats for CCHFV-specific IgG using an indirect fluorescent antibody test and ELISA, we found CCHFV antibody–positive goats along the analyzed border region with India, indicating widespread distribution of CCHFV in this area.